Boosting the Fill Factor through Sequential Deposition and Homo Hydrocarbon Solvent toward Efficient and Stable All‐Polymer Solar Cells. Issue 48 (3rd November 2022) - Wang, Yan; Yu, Han; Wu, Xin; Zhao, Dan; Zhang, Shoufeng; Zou, Xinhui; Li, Bo; Gao, Danpeng; Li, Zhen; Xia, Xinxin; Chen, Xiankai; Lu, Xinhui; et al.
Abstract: All‐polymer solar cells (all‐PSCs) have achieved impressive progress in photovoltaic performance and stabilities recently. However, their power conversion efficiencies (PCEs) still trail that of small‐molecular acceptor‐based organic solar cells (>19%) mainly because of the inferior fill factor (FF). Herein, a combined homo hydrocarbon solvent and sequential deposition (SD) strategy is presented to boost the FF of rigid all‐PSCs to 77.7% and achieve a superior PCE of 17.7% with excellent stability, which is among the highest efficiencies reported for all‐PSCs thus far. Meanwhile, a remarkable PCE of 14.5% is realized for flexible all‐PSCs with outstanding mechanical stability. The blend film morphologies measurements suggest that the SD method enables the formation of an ideal pseudo‐bilayer film with bicontinuous interdigitated structure and ordered polymer packing. The numerical simulation result indicates that the FF enhancement mainly results from the efficient exciton diffusion dynamics, increased carrier mobilities, and more balanced electron/hole mobility ratio induced by the developed SD method. This is also confirmed by the FF loss analysis, which manifests that the reduced series resistance and increased shunt resistance are the main reasons for the reduction of FF loss. This work provides a promising strategy to fabricate highly efficient and stable all‐PSCs to promote their future development and practical manufacturing. Abstract : A combined homo hydrocarbon solvent sequential deposition process is demonstrated for all‐polymer solar cells (all‐PSCs) fabrication. A champion power conversion efficiency (PCE) of 17.7% with a remarkably high fill factor of 77.7% is achieved for rigid all‐PSCs based on PM6:PY‐V‐γ, while the corresponding flexible device also enables an impressive PCE of 14.5% with excellent storage, thermal, photo, and mechanical stabilities.